2015
DOI: 10.1016/j.landusepol.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Farm size and participation in agri-environmental measures: Farm-level evidence from Slovenia

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden. Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen. Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 37 publications
(58 reference statements)
2
41
0
2
Order By: Relevance
“…These results indicate that greater OMA adoption occurred on smaller farms. Other studies describe a similar trend whereby the use of integrated and organic soil management practices was greater on smaller farms (Rangarajan et al, 2002; Unay Gailhard and Bojnec, 2015; Williams, 1999). While more studies report a positive adoption of soil management practices such as conservation tillage with farm size where specialized equipment is scalable (Prokopy et al, 2008), we presume obtaining OMA of sufficient quantity and quality makes OMA adoption more amendable to smaller farms.…”
Section: Resultsmentioning
confidence: 66%
“…These results indicate that greater OMA adoption occurred on smaller farms. Other studies describe a similar trend whereby the use of integrated and organic soil management practices was greater on smaller farms (Rangarajan et al, 2002; Unay Gailhard and Bojnec, 2015; Williams, 1999). While more studies report a positive adoption of soil management practices such as conservation tillage with farm size where specialized equipment is scalable (Prokopy et al, 2008), we presume obtaining OMA of sufficient quantity and quality makes OMA adoption more amendable to smaller farms.…”
Section: Resultsmentioning
confidence: 66%
“…The higher participation of the young farmers could be because the organic enterprise is relatively new and more innovative; while the less participation of older farmers could be because of its high labour requirements. A number of studies have shown that young farmers significantly adopt organic enterprises more than older farmers (Vanslembrouck et al, 2002;Gailhard and Bojnec, 2015;Nandi et al, 2015). These studies have also consistently shown innovation and profits as the main drivers of organic adoption among young people.…”
Section: Resultsmentioning
confidence: 98%
“…Further analysis showed that 45% of the farmers had grown organic pineapples for less than 5 years, while 24% in 6 -10 years, and 31% between 11-20 years. With respect to other countries, organic fruit and vegetable production is more recent in India, where the organic enterprises averagely started in 2008 (Nandi et al, 2015); while in Central Germany, organic farming was practiced since 1993 (Gailhard and Bojnec, 2015). Farmers who had more land under organic pineapples managed the enterprises for more years than their counterparts with less land.…”
Section: Resultsmentioning
confidence: 99%
“…Most of these studies have used discrete response models such as logit binary models, as this modeling framework allows for estimates to be made of the probability of an individual deciding between one alternative and another [14]. In particular, the binary logit model is widely used to analyze the decision of farmers to participate in environmental programs [15,16], as well as to adopt technology packages [17][18][19][20]. However, the application of such models to study the long term sustainability or the abandonment of a project has received less attention.…”
Section: Introductionmentioning
confidence: 99%
“…Results of such studies indicate that the decision to adopt or participate is often related to the participants' characteristics [15,19,21], social capital [16,20,22,24,25] production characteristics [16,18,20,21,24,25], and the characteristics of the project [20,26]. Consequently, in this project, the jatropha suppliers' decision to participate was analyzed by considering explanatory variables related to the suppliers' characteristics, social capital, production characteristics and perceptions on the characteristics of the project.…”
Section: Introductionmentioning
confidence: 99%